Rút gọn biểu thức: P = 2 n + 4 - 2 ( 2 n ) 2 ( 2 n + 3 ) .
A. 2 n + 1
B. 1 - 2 n
C. 7 4
D. 7 8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=\(2^{n-1}+2.2^n+3-8.2^{n-4}-16.2^n=\)\(\frac{2^n}{2}+2.2^n-8.\frac{2^n}{2^4}-16.2^n+3\)
=\(2^n\left(\frac{1}{2}+2-\frac{8}{16}-16\right)+3\)=\(-14.2^n+3\)
a) \(3^n+3^{n+2}=3^n.\left(1+3^2\right)=3^n.\left(1+9\right)=10.3^n\)
b) \(1,5.2^n-2^{n-1}=1,5.2^{1+n-1}-2^{n-1}=1,5.2.2^{n-1}-2^{n-1}\)
\(=3.2^{n-1}-2^{n-1}=2^{n-1}.\left(3-1\right)=2^{n-1}.2=2^n\)
\(=\frac{\left(a+2\right)\left(a-1\right)}{a^n\left(a-3\right)}.\left[\frac{\left(a+2-a\right)\left(a+2+a\right)}{4\left(a-1\right)\left(a+1\right)}-\frac{3}{a.\left(a-1\right)}\right]\) (Đk : x khác 0 ; 3 ; - 1 ; 1
\(=\frac{\left(a+2\right)\left(a-1\right)}{a^n\left(a-3\right)}.\left[\frac{4\left(a+1\right)}{4\left(a-1\right)\left(a+1\right)}-\frac{3}{a\left(a-1\right)}\right]\)
\(=\frac{\left(a+2\right)\left(a-1\right)}{a^n\left(a-3\right)}.\left[\frac{1}{a-1}-\frac{3}{a\left(a-1\right)}\right]\)
\(=\frac{\left(a+2\right)\left(a-1\right)}{a^n\left(a-3\right)}.\frac{a-3}{a\left(a-1\right)}=\frac{a+2}{a^{n+1}}\)
n(n+1)(n+2)+(n+3)(n+4)
=(n2+n)(n+2)+n2+7n+12
=n3+3n2+2n+n2+7n+12
=n3+(3n2+n2)+(2n+7n)+12
=n3+4n2+9n+12
Chọn đáp án D